Overcoming Global Issues on Gender-Biased in Adjudication Process: The Role of Companions for Rape Victims - Putri, Ria Wierma; Laila, Siti Noor; Putri, Yunita Maya; Sabatira, Febryani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine the extent of state protection towards rape victims in the litigation process under existing laws. However, the phenomenon of gender bias by the surrounding society and law enforcers mostly leads to victim-blaming, which prevents them from reporting the case. Moreover, the study argues that it is necessary to provide a victim's companion at the trial, particularly in the victim-witness examination process, to support them contribute detailed information in a comfortable and secure condition. This study uses a normative-empirical legal approach with primary and secondary data sources. The study discusses the extent of rape victims' protection and the need for companion in litigation process. The results showed that the State had made its efforts to protect women of rape victims by enforcing a sequence of laws beyond the Criminal Code such as Law No. 11 of 2012 concerning the Juvenile Criminal Justice System and Supreme Court Regulation No. 3 of 2017 concerning Guidelines in Adjudicating Women's Cases Against the Law. However, these efforts are deemed insufficient to provide proper protection for rape victims, as evidenced by the significant development of rape cases due to legal enforces' insensibility dealing with women as victims in the litigation process.